Ultralow Dose of Naloxone as an Adjuvant to Intrathecal Morphine Infusion Improves Perceived Quality of Sleep but Fails to Alter Persistent Pain: A Randomized, Double-blind, Controlled Study. Issue 11 (November 2015) - Block, Linda; Lundborg, Christopher; Bjersing, Jan; Dahm, Peter; Hansson, Elisabeth; Biber, Björn
Abstract : Introduction: This randomized, cross-over, double-blind, controlled study of continuous intrathecal morphine administration in patients with severe, long-term pain addresses whether the supplementation of low doses of naloxone in this setting is associated with beneficial clinical effects. Methods: All of the study subjects (n=11) provided informed consent and were recruited from a subset of patients who were already undergoing long-term treatment with continuous intrathecal morphine because of difficult-to-treat pain. The patients were (in a randomized order) also given intrathecal naloxone (40 ng/24 h or 400 ng/24 h). As control, the patients' ordinary dose of morphine without any additions was used. The pain (Numeric Rating Scale, NRS) during activity, perceived quality of sleep, level of activity, and quality of life as well as the levels of several proinflammatory and anti-inflammatory cytokines in the blood were assessed. The prestudy pain (NRS during activity) in the study group ranged from 3 to 10. Results: A total of 64% of the subjects reported improved quality of sleep during treatment with naloxone at a dose of 40 ng per 24 hours as compared with 9% with sham treatment ( P =0.024). Although not statistically significant, pain was reduced by 2 NRS steps or more during supplemental treatment with naloxone in 36% of subjects when using the 40 ng per 24 hours dose and in 18% of the subjects when using naloxone 400 ng per 24 hours dose. The corresponding percentage among patients receiving unaltered treatment was 27%. Conclusions: To conclude, the addition of an ultralow dose of intrathecal naloxone (40 ng/24 h) to intrathecal morphine infusion in patients with severe, persistent pain improved perceived quality of sleep. We were not able to show any statistically significant effects of naloxone on pain relief, level of activity, or quality of life. Abstract : Supplemental Digital Content is available in the text.